1986
DOI: 10.1080/15287398609530814
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary changes resulting from subchronic exposure to cadmium chloride aerosol

Abstract: Fischer-344 rats were exposed to 0.0, 0.3, 1.0, or 2.0 mg Cd/m3 as CdCl2 aerosol for 6 h/d, 5 d/wk, for 62 exposure days. Exposure to 2.0 mg Cd/m3 resulted in rapid weight loss, and all of the animals died within the first 45 exposure days. As a group, female rats survived significantly longer than the males. Exposure to Cd resulted in dose-dependent increases in lung weight. The increased weight was the result of additional tissue mass rather than edema. Both connective-tissue components, elastin and collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The increase in rat lung weight suggests hypercellularity due to a chronic inflammatory response, the lung's own repair process, and/or new lung tissue (including fibrosis), which reflected across each of the rodent models as increases in protein, DNA as well as elastin and hydroxyproline (i.e., collagen). Such changes have been reported previously [40,[59][60][61].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The increase in rat lung weight suggests hypercellularity due to a chronic inflammatory response, the lung's own repair process, and/or new lung tissue (including fibrosis), which reflected across each of the rodent models as increases in protein, DNA as well as elastin and hydroxyproline (i.e., collagen). Such changes have been reported previously [40,[59][60][61].…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, hypoxia appears to be a stimulus for lung growth and expansion [64], which parallels the hypoxia, likely experienced in the rats with peribronchiolar fibrosis. Abnormal lung growth has also been reported in rats exposed to acrolein [40], cadmium chloride [61], silica [65,66], and by irradiation [67].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies in the literature reported the weight loss, whereas no significant weight gain was seen in rats exposed to this level of CdCl 2 . Kutzman and coworkers exposed male and female rats to 0, 0.3, 1.0, or 2.0 mg Cd/m 3 6 h per day, 5 days per week for a total of 62 exposures at the end of which marked weight loss were observed in the highest dose group (Kutzman, et al, 1986). A study from Turkey also showed a CdCl 2 caused body weight loss, was reversed by Licopene (Rencuzogullari and Erdogan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…After long term repeated exposure to Cd, the neurotoxic effects in adolescent or adult rats, however, may be different. On inhalation of CdCl 2 aerosols (5 days/week, 6 h/day, for 12 weeks) rats showed no change at 0.33 mg Cd/m3, but there was a significant increase of relative brain weight at 1.034 mg Cd/m 3 36. Oral or intraperitoneal Cd dosing induced aggressive behaviour,15increased failure to respond to a conditioned or unconditioned stimulus,16 decreased locomotor, exploratory, and rearing activities 13…”
Section: Discussionmentioning
confidence: 99%